Antagonism of microRNA function in zebrafish embryos by using locked nucleic acid enzymes (LNAzymes) - Suryawanshi, Hemant; Lalwani, Mukesh Kumar; Ramasamy, Soundhar; Rana, Rajiv; Scaria, Vinod; Sivasubbu, Sridhar; Maiti, Souvik (Chembiochem, 2012)
MicroRNAs (miRNAs) have crucial functions in many cellular processes, such as differentiation, proliferation and apoptosis; aberrant expression of miRNAs has been linked to human diseases, including cancer. Tools that allow specific and efficient knockdown of miRNAs would be of immense importance for exploring miRNA function. Zebrafish serves as an excellent vertebrate model system to understand the functions of miRNAs involved in a variety of biological processes. We designed and employed a strategy based on locked nucleic acid enzymes (LNAzymes) for in vivo knockdown of miRNA in zebrafish embryos. We demonstrate that LNAzyme can efficiently knockdown miRNAs with minimal toxicity to the zebrafish embryos.
Keywords: enzymes; locked nucleic acids; microRNA; morpholino; zebrafish

Morphological effects of G-quadruplex stabilization using a small molecule in zebrafish - Agarwal, Tani; Lalwani, Mukesh Kumar; Kumar, Santosh; Roy, Saumya; Chakraborty, Tushar Kanti; Sivasubbu, Sridhar; Maiti, Souvik (Biochemistry, 2014)
Zebrafish (Danio rerio) embryos are transparent and advantageous for studying early developmental changes due to ex utero development, making them an appropriate model for studying gene expression changes as a result of molecular targeting. Zebrafish embryos were injected with a previously reported G-quadruplex selective ligand, and the phenotypic changes were recorded. We report marked discrepancies in the development of intersegmental vessels. In silico analysis determined that the putative G-quadruplex motif occur in the upstream promoter region of the Cdh5 (N-cadherin) gene. A real-time polymerase chain reaction-based investigation indicated that in zebrafish, CDH-2 (ZN-cad) was significantly downregulated in the ligand-treated embryos. Biophysical characterization of the interaction of the ligand with the G-quadruplex motif found in this promoter yielded strong binding and stabilization of the G-quadruplex with this ligand. Hence, we report for the first time the phenotypic impact of G-quadruplex targeting with a ligand in a vertebrate organism. This study has unveiled not only G-quadruplex targeting in non-human animal species but also the potential that G-quadruplexes can provide a ready tool for understanding the phenotypic effects of targeting certain important genes involved in differentiation and developmental processes in a living eukaryotic organism.

G-quadruplex motif at the 3' end of sgRNAs improves CRISPR-Cas9 based genome editing efficiency - Nahar, Smita; Sehgal, Paras; Azhar, Mohammad; Rai, Manish; Singh, Amrita; Sivasubbu, Sridhar; Chakraborty, Debojyoti; Maiti, Souvik (Chemical Communications, 2018)
Originating as a component of prokaryotic adaptive immunity, the type II CRISPR/Cas9 system has been repurposed for targeted genome editing in various organisms. Although Cas9 can bind and cleave DNA efficiently under in vitro conditions, its activity inside a cell can vary dramatically between targets owing to differences between genomic loci and availability of enough Cas9/sgRNA (single guide RNA) complex molecules for cleavage. Most methods to improve CRISPR/Cas9 activity have so far relied on Cas9 protein engineering or base modifications in the sgRNA sequence. Here we demonstrate that a structure based rational design of sgRNAs can enhance the efficiency of Cas9 cleavage in vivo. By appending a naturally forming RNA G-quadruplex motif to the 3′ end of sgRNAs we can improve its stability and target cleavage efficiency in zebrafish embryos without inducing off-target activity, thereby underscoring its value in the design of better and optimized genome editing triggers.

Chronic systemic exposure to IL6 leads to deregulation of glycolysis and fat accumulation in the zebrafish liver - Singh, Manoj K.; Jayarajan, Rijith; Varshney, Swati; Upadrasta, Sindhuri; Singh, Archana; Yadav, Rajni; Scaria, Vinod; Sengupta, Shantanu; Shanmugam, Dhanasekaran; Shalimar; Sivasubbu, Sridhar; Gandotra, Sheetal; et al. (Biochimica ET Biophysica Acta-Molecular and Cell Biology of Lipids, 2021)
Inflammation is a constant in Non-Alcoholic Fatty Liver Disease (NAFLD), although their relationship is unclear. In a transgenic zebrafish system with chronic systemic overexpression of human IL6 (IL6-OE) we show that inflammation can cause intra-hepatic accumulation of triglycerides. Transcriptomics and proteomics analysis of the IL6-OE liver revealed a deregulation of glycolysis/gluconeogenesis pathway, especially a striking down regulation of the glycolytic enzyme aldolase b. Metabolomics analysis by mass spectrometry showed accumulation of hexose monophosphates and their derivatives, which can act as precursors for triglyceride synthesis. Our results suggest that IL6-driven repression of glycolysis/gluconeogenesis, specifically aldolase b, may be a novel mechanism for fatty liver. This mechanism may be relevant for NAFLD in lean individuals, an emerging class of NAFLD prevalent more in Asian Indian populations.
Keywords: Aldolase b; DHAP; Inflammation; Interleukin 6; Lean NAFLD; Non-alcoholic fatty liver

G4-binding drugs, chlorpromazine and prochlorperazine, repurposed against COVID-19 infection in hamsters - Roy, Shuvra Shekhar; Sharma, Shalu; Rizvi, Zaigham Abbas; Sinha, Dipanjali; Gupta, Divya; Rophina, Mercy; Sehgal, Paras; Sadhu, Srikanth; Tripathy, Manas Ranjan; Samal, Sweety; Maiti, Souvik; Scaria, Vinod; et al. (Frontiers in Molecular Biosciences, 2023)
The COVID-19 pandemic caused by SARS-CoV-2 has caused millions of infections and deaths worldwide. Limited treatment options and the threat from emerging variants underline the need for novel and widely accessible therapeutics. G-quadruplexes (G4s) are nucleic acid secondary structures known to affect many cellular processes including viral replication and transcription. We identified heretofore not reported G4s with remarkably low mutation frequency across >5 million SARS-CoV-2 genomes. The G4 structure was targeted using FDA-approved drugs that can bind G4s - Chlorpromazine (CPZ) and Prochlorperazine (PCZ). We found significant inhibition in lung pathology and lung viral load of SARS-CoV-2 challenged hamsters when treated with CPZ or PCZ that was comparable to the widely used antiviral drug Remdesivir. In support, in vitro G4 binding, inhibition of reverse transcription from RNA isolated from COVID-infected humans, and attenuated viral replication and infectivity in Vero cell cultures were clear in case of both CPZ and PCZ. Apart from the wide accessibility of CPZ/PCZ, targeting relatively invariant nucleic acid structures poses an attractive strategy against viruses like SARS-CoV-2, which spread fast and accumulate mutations quickly.
Keywords: Conserved motif; FDA-approved drugs; G-quadruplex binding drugs; hamster model of COVID-19; RNA G-quadruplex